2014
DOI: 10.1371/journal.pone.0085195
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Network Analysis-Based Identification of Antimicrobial Drug Targets in Category A Bioterrorism Agents

Abstract: The 2001 anthrax mail attacks in the United States demonstrated the potential threat of bioterrorism, hence driving the need to develop sophisticated treatment and diagnostic protocols to counter biological warfare. Here, by performing flux balance analyses on the fully-annotated metabolic networks of multiple, whole genome-sequenced bacterial strains, we have identified a large number of metabolic enzymes as potential drug targets for each of the three Category A-designated bioterrorism agents including Bacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…holartica, F. tularensis mediasatica, and F. tularensis spp. Neither NMN synthetase nor NAD synthetases were identified to be essential in our study (Ahn et al, 2014). F. tularensis (Biovar type A) is highly virulent and occurs predominantly in North America.…”
Section: Metabolic Targets In Francisella Tularensismentioning
confidence: 54%
See 1 more Smart Citation
“…holartica, F. tularensis mediasatica, and F. tularensis spp. Neither NMN synthetase nor NAD synthetases were identified to be essential in our study (Ahn et al, 2014). F. tularensis (Biovar type A) is highly virulent and occurs predominantly in North America.…”
Section: Metabolic Targets In Francisella Tularensismentioning
confidence: 54%
“…F. tularensis can be grouped into four distinct subspecies; F. tularensis spp. Ahn et al (2014) identified a total of 46 single essential enzymes across the seven species and the majority of them were in the vitamins, cofactors, and cell-wall biosynthesis pathways. holartica, F. tularensis mediasatica, and F. tularensis spp.…”
Section: Metabolic Targets In Francisella Tularensismentioning
confidence: 99%
“…A genome-scale model of E. coli was used to provide the organism with direct biocatalytic routes to 1,4-butanediol [212] and to identify better drug targets or biosynthetic pathways for antibiotics [213][214][215][216].…”
Section: Modellingmentioning
confidence: 99%
“…The F. tularensis metabolic and virulence factors allowing this bacterium to resist the attack by phagocytic cells and adapt to their intracellular niche can be considered potential targets for the development of new therapeutic strategies. Analyzing metabolic networks in category A bioterrorism agents, Ahn et al [23] identified enzymes that could potentially serve as new antimicrobial drug targets, especially those belonging to the biosynthesis pathways of vitamins, cofactors and the bacterial cell wall. Using an integrated in silico/in vitro approach, Chaudhury et al [24] also selected compounds with potential F. tularensis metabolism inhibitory activity, especially by targeting pantetheine-phosphate adenylyltransferase, an enzyme involved in coenzyme A biosynthesis.…”
Section: F Tularensis As a Bioterrorism Agentmentioning
confidence: 99%